Triazole functionalized acyclic cucurbit[n]uril-type receptors: host·guest recognition properties. Issue 22 (21st May 2019) - Xue, Weijian; Zavalij, Peter Y.; Isaacs, Lyle
Abstract : The synthesis, characterization, and molecular recognition properties of2–4 toward organic ammonium ions in water is reported. Abstract : We report the synthesis of three new triazole functionalized acyclic CB[ n ]-type receptors (2–4 ) by click chemistry. The compounds have good solubility in water (≥8 mM) and do not undergo strong self-association ( K s ≤ 903 M −1 ). We measured the binding constants of2–4 toward guests9–24 and compared the results to those obtained for the prototypical acyclic CB[ n ]-type receptor1 . The X-ray crystal structure of4 is also described.